Facilities and Service Quality as Predictors of Visitor Satisfaction at Belibis Island Tourism Attraction, Solok City - Jodi Perdana Putra; Hijriyantomi Suyuthie (Journal of Multidimensional Management, 2026)
This study examines facilities and service quality as predictors of visitor satisfaction at Belibis Island Tourism Attraction in Solok City. A quantitative cross-sectional survey was conducted with 264 visitors selected through purposive screening after a Slovin-based sample target was established. Eligible respondents had direct experience with the attraction's facilities and visitor services. Data were collected using a five-point Likert-scale questionnaire and analyzed with descriptive statistics, regression diagnostics, and multiple linear regression in SPSS 20. Facilities (mean = 2.34), service quality (mean = 2.25), and visitor satisfaction (mean = 2.27) were all classified as poor. The overall model was significant (F = 756.355, p < 0.001) and explained 85.3% of the variance in visitor satisfaction. Facilities were a positive predictor (B = 0.546, beta = 0.356, p < 0.001), while service quality showed the stronger relative coefficient (B = 0.723, beta = 0.585, p < 0.001). The high R2 should be interpreted cautiously because all constructs were measured in the same cross-sectional questionnaire. The findings support short-term priorities in safety-critical facility repair, staffing, and basic service standards, followed by preventive maintenance and continuous visitor-feedback monitoring.